(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2024)
Abstract: The application of automation technology in industry is growing rapidly, especially in the chemical industry. The more advanced the level of industrial development in a country or region, the greater the number and types of industries. By integrating technological, machine, and human resources, it provides major changes to the industrial sector to get priority for development because it can make a significant contribution to the national economy. Several chemical industries have developed, including the petrochemical industry, agrochemicals, and so on. The chemical industry produces various chemical products to meet the needs of the Indonesian people. In human life, it is inseparable from the use of chemicals produced by the chemical industry. The increase in the number of chemical industries will also increase the potential for danger and risk. The danger of fire is one of the potentials that can have a major impact and even the risk of death and serious burns to humans. In addition to the risk to humans, fire also damages company assets and pollutes the environment. Therefore, the author conducted a study in one of the chemical industries in the city of Cilegon which has great potential for danger and high risk. This potential fire hazard is triggered by the activity of unloading flammable chemicals from ships to storage tanks. The purpose of this study is to identify hazards and assess risks in the activity of unloading flammable chemicals from ships to storage tanks. This study uses the Hazard Identification, Risk Assessment and Control (HIRAC) method. The results of this study are to determine the level of fire risk in the activity of unloading flammable chemicals from ships to storage tanks and to prepare prevention and mitigation strategies